The Effect of Economic Growth and Income Inequality on Poverty in Central Sulawesi Province Period 2011-2022 - Ramla Ilham Darise (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to ascertain how differences in income and poverty in Central Sulawesi Province are affected by the 2011-2020 economic growth. The poverty reduction rate in Central Sulawesi Province is the best trading location for Sulawesi. However, the poverty rate for Sulawesi Province is still higher than the average across Sulawesi Province. Secondary data for this type of research were obtained from the Central Bureau of Statistics, and multiple linear regression was used as a data analysis tool. The results show that between 2011 and 2020, income attractiveness in Central Sulawesi Province has a positive and negligible impact on poverty, but economic expansion has a minimal long-term impact on poverty as well